If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3n + -6(3n + -6) = 111 Reorder the terms: 3n + -6(-6 + 3n) = 111 3n + (-6 * -6 + 3n * -6) = 111 3n + (36 + -18n) = 111 Reorder the terms: 36 + 3n + -18n = 111 Combine like terms: 3n + -18n = -15n 36 + -15n = 111 Solving 36 + -15n = 111 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-36' to each side of the equation. 36 + -36 + -15n = 111 + -36 Combine like terms: 36 + -36 = 0 0 + -15n = 111 + -36 -15n = 111 + -36 Combine like terms: 111 + -36 = 75 -15n = 75 Divide each side by '-15'. n = -5 Simplifying n = -5
| y+15-2=0 | | k=1.6*655 | | u+21=8 | | (5x+6)(2x+1)= | | 1.1(2.5x-3.5)=11.2 | | -12(0)+16=16+10(0) | | 2v-8(8-2v)=-82 | | (4x+4)(2x+1)= | | X+14=152 | | -12+16=16+10 | | (-x+1)(3x-8)= | | -8-9x=163 | | k=1.6*430 | | I=1.6*430 | | y=-18x^2+321 | | -12+16=16+0 | | (x-8)(x+5)= | | X-25=66 | | 25b^2+15b= | | y=-16x^2+24 | | (x)(3x^2+y^3+7)= | | (5+4x)(5-4x)= | | (2x-1)=(x-2)(4x+3) | | 4.7+10x=8x+14.9 | | (2x^2-2x+3)(-x)= | | 52=8y+8 | | y=--2-3 | | -12n+16=16+10n | | 2x^2+9=49 | | 40*60=30*x | | 11n-19n=48 | | (-3x)(-5x^2+y)= |